Sociocultural Factors Influencing Gestational Diabetes Mellitus Outcomes - Verlina Gita; Irma Afifa (Interdisciplinary Journal of Ethnopsychiatric Nursing, 2025)
Gestational diabetes mellitus (GDM) represents a growing global health challenge with significant maternal and neonatal consequences, yet cultural factors influencing its outcomes remain underexplored despite persistent ethnic disparities in prevalence and complications. This literature review synthesises evidence on how cultural determinants shape GDM self-management and perinatal outcomes across diverse populations. Peer-reviewed studies were identified through systematic database searches of PubMed, PMC, Google Scholar, and Web of Science using targeted keywords related to GDM, ethnicity, cultural influences, and outcomes, with no date restrictions but emphasis on contemporary research; 8 studies were selected for narrative synthesis based on relevance to cultural domains, including qualitative inquiries, cohort analyses, and systematic reviews from multi-ethnic settings. Findings reveal marked ethnic variations: Asian women exhibit high GDM prevalence yet favorable outcomes, while Black and indigenous groups face elevated risks of preeclampsia, preterm birth, and neonatal hypoglycemia linked to culturally incongruent dietary advice, low health literacy, and psychosocial stressors; cultural staples like rice-based dishes or starchy tubers often conflict with management recommendations, reducing adherence by 40-50%, and language-discordant care erodes trust and follow-up. These insights underscore the need for culturally tailored interventions, such as family-inclusive counselling and ethnicity-specific meal plans, to mitigate disparities and enhance equity in GDM care. Future research should prioritise randomised trials of adapted strategies and longitudinal studies in underrepresented regions to establish causality and scalability.